2018
DOI: 10.1186/s41118-018-0040-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of simple methods for regional mortality forecasts

Abstract: BackgroundIn recent decades, considerable research effort has been dedicated to improving mortality forecasting methods. While making valuable contributions to the literature, the bulk of this research has focused on national populations—yet much planning and service delivery occurs at regional and local scales. More attention needs to be paid to subnational mortality forecasting methods.ObjectiveThe objective of this study was to evaluate eight fairly simple methods of regional mortality forecasting, focusing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…These studies focused on regional differences, or changes in health levels, and found significant associations between regional differences in health levels, particularly in regional mortality. Many studies have shown that socio-economic factors, rather than natural environment, play an important role in contributing to regional differences in mortality (6,8,(12)(13)(14)(15)(16). Their findings empirically proved the influence of medical resource on individual health level.…”
Section: Literature Reviewmentioning
confidence: 98%
“…These studies focused on regional differences, or changes in health levels, and found significant associations between regional differences in health levels, particularly in regional mortality. Many studies have shown that socio-economic factors, rather than natural environment, play an important role in contributing to regional differences in mortality (6,8,(12)(13)(14)(15)(16). Their findings empirically proved the influence of medical resource on individual health level.…”
Section: Literature Reviewmentioning
confidence: 98%
“…A national life table projection was created for the Australian population overall based on Ediev’s ( 2008 ) mortality forecasting method, with birthplace-specific life expectancy assumed to move in concert with this projection but at fixed lower or higher values according to 2011-2016 life expectancy differentials. Birthplace-specific age-sex-specific death rates corresponding to assumed life expectancies were calculated from the national life tables (Wilson, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…State and Territory life expectancy at birth was assumed to move in parallel with national life expectancy into the future. Age-specific death rates corresponding to each life expectancy assumption were selected from the national mortality projections (Wilson 2018) for every jurisdiction except the Northern Territory. A separate mortality projection was prepared for the NT because of its unique mortality rate age profile.…”
Section: Datamentioning
confidence: 99%